A comparative study of the mechanical and electrical activities of the heart according to the energy systems of advanced playersA comparative study of the mechanical and electrical activities of the heart according to the energy systems of advanced player - Salman, Thaer Dawood; Al Majed, Amjad Abdul Hamid (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to identify the mechanical and electrical activities of the heart according to the energy systems of advanced players and to detect the differences between the energy systems in terms of the mechanical and electrical activities of the heart for advanced players. It was clear from the results of the significance of the differences between the three groups according to the energy systems of the advanced players in all research variables that (the non-oxygenic system "Lactic"), which represents the advanced players in the arches (800 m, 1500 m) was the first in most tests of mechanical and electrical activities of the heart, which is (Margaria-Kalamen, Wingate, systolic muscle strength of the heart FC, Stroke Volume SV, End Diastolic Volume EDV, Ejection Fraction Percentage EF, and Left Ventricular Diastolic Dimension( LVDD). The study recommended the need for trainers to use the indicators of the mechanical and electrical activities of the heart in knowing the functional susceptibility of players in each energy system in training players and conducting similar studies to measure mechanical and electrical indicators of the heart according to energy systems on sporting activities that were not addressed in the current study.